ANALISIS NILAI TAMBAH INFORMASI LAPORAN ARUS KAS - Zaki Baridwan (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
The Indonesian Institute of Accountants published the Statement ofFinancial Accounting Standards No.Z